Pozytywne i negatywne przesłanki orzeczenia rozwodu w prawie cywilnym w świetle orzecznictwa Sądu Najwyższego i sądów powszechnych – zarys problematyki - Krawczyk, Michał (Ius Matrimoniale, 2018)
Marriage is a relationship of a woman and a man combining a spiritual (sacramental) and civil nature. The binding principle of secularity of the state and law means that sacramental marriage undercomes both: canonic law and civil law. The decision of the church court about the validity or termination of a sacramental marriage cannot have an influence the verdict of the state court about the validity or termination of a marriage and vice versa. Secular law, in contrast to canon law, permits the dissolution of a marriage by divorce. The relevant regulations in the Polish legal order are included in art. 56 of the Family and Guardianship Code (hereinafter k.r.o). The Code provides for the possibility of divorce in the case of two positive reasons and the absence of three negative ones. The normative regulation seems clear, but nonetheless it contains many general clauses, which application may raise justified doubts in specific situations. The rich jurisprudence of the Supreme Court and common courts regarding the subject matter is a great help in the interpretation of this regulation (tłumaczenie: dr Anna Świrska, WNEiP, UPH w Siedlcach).